Assessing the costs of a haulage regime - Wills-Johnson, Nick (Centre for Research in Applied Economics, Curtin Business School, 2008)
The provision of third-party access to rail infrastructure in WA?s Pilbara region has been a contentious issue over the past decade. The most recent endeavour proposed by the State Government involves a haulage regime, whereby incumbents would be required to haul the wagons of third parties seeking access to the line. This paper explores the likely costs of such a regime on the host railways, by examining the impacts of voluntary haulage regimes on US Class One Railways, where they are well-established. It finds that haulage regimes are a cost effective means for US railways to reduce their haulage costs, and that they thus might play a role in the Pilbara. However, consideration of whole-of-system costs, congestion and appropriate pricing are key issues. This paper explores these issues, and proposes a simple pricing mechanism which would ensure fair, efficient haulage with only very limited regulatory involvement.